2021
DOI: 10.1111/scd.12585
|View full text |Cite
|
Sign up to set email alerts
|

The role of double‐step advancement genioplasty and bilateral coronoidectomy in Nager Syndrome: A case report

Abstract: Aim To report the surgical management of bilateral mandibular coronoid processes hyperplasia and mandibular retrognathism associated with trismus and convex facial profile in an individual diagnosed with Nager syndrome (NS). Case report A 21 years old female was referred to the Department of Oral and Maxillofacial Surgery, presenting limited mouth opening and an unpleasant convex facial profile. The tomography exhibited hyperplasia of mandibular coronoid processes with no evidence of intracapsular ankylosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, it is considered to be a separate clinical entity of the disease (Dixon et al, 2017). There are 3 publications involving 4 patients with restricted mouth opening and CPH (Schlieve et al, 2012; Trindade et al, 2021; Wu et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is considered to be a separate clinical entity of the disease (Dixon et al, 2017). There are 3 publications involving 4 patients with restricted mouth opening and CPH (Schlieve et al, 2012; Trindade et al, 2021; Wu et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Pasetti et al (2016) reported one patient with Carey-Finema-Ziter syndrome with CPH. Trindade et al, 2021;Wu et al, 2017).…”
Section: Carey-finema-ziter Syndromementioning
confidence: 99%